Laser induced arc dynamics destabilization in laser-arc hybrid welding - Mu, Zhongyan; Chen, Xin; Hu, Renzhi; Lin, Sanbao; Pang, Shengyong (IOP Publishing, 2019)
The interaction between laser and arc plasma is a central issue in laser-arc hybrid welding. We report a new interaction phenomenon called laser destabilizing arc dynamics in kilowatt fiber laser-TIG hybrid welding of 316L stainless steel. We found the laser action significantly oscillates the arc tail with a 1–3 kHz high frequency. Direct numerical simulation demonstrates that the destabilization mechanism is due to the high-speed oscillated metal vapor ejecting from the mesoscopic keyhole. More interestingly, the high-speed metal vapor could contrict the arc plasma by physical shielding. This provides a fundamentally different explanation from the generally adopted metal vapor ionization theory for laser constrict arc plasma phenomenon. Also, the results substantiate that the arc plasma cannot easily enter into the keyhole because of the violent metal vapor.
Keywords: keyhole; laser-induced vapor; arc plasma; hybrid welding